(3dhGeY GdJHjGf aj TQM GdQSGdI GdehSheI HGdHjGf aj Yde GdHjGfs - (3YHO Gddg Hf Ydj Hf YHO GdQMef ShjOGf GdOedjLj,J (B1234 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi UhQ Tcd GdEfSGf hHYO agPG TQM Ydi ebOeJi GdehSheI HGdHjGf ai Yde GdHjGf HSe Gddg GdQMef GdQMje fMeO Ci fUa HGdLejd s
(3BNQgG (B:s
(3efaQOkG HJOHjQ GdeedcI jSeY hjQi hjYWi bHd Cf jNdb GdYHGO hfUM Ndbge hOdge Ydi eG ajg GdSYGOg hCf jLYd gPG GdcJGH NGdUkG dhLgg GdcQje Efg QDha QMje hgh MSHi hfYe Gdhcjd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B16s
(3GdfSNI HgG MhGTs
(3HChdgG hBNQg fbhdHgG fXGe GdJYbjHIJUhas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B107 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B89s
Keywords: (3GdeLGejYs